Wound care in a child suffering from Stevens-Johnson syndrome in PICU: case report - Carlotta Zanetti (Firenze University Press, 2024)
Stevens-Johnson Syndrome is considered a life-threatening adverse drug reaction.  The pathogenesis of these syndromesis still unclear, but several drugs, such as anticonvulsivants and antibiotics, and especially sulfonamides, non-steroidal anti-infiammatorydrugs, and allopurinol were predominantly suspected of triggering this reaction. A 5-year-old boy patient who came to hospital attention for an urticarial reaction developed after taking amoxicillin, then a recent scarlet fever acquired by brother. Due to the worsening of the lesions, he was admitted to our PICU after being intubated for deterioration of the respiratory dynamics and safe treatment of secretions. Nursing care is crucial: care of patient hospitalized with Stevens-Johnson syndrome and Toxic Epidermal Necrolysis consists of wound care, infection prevention, comfort management, hydration and nutrition, psychosocial support, and prevention of long-term complications. For all patients with SJS and TEN, it is essential to perform a total body daily evaluation of the skin. If the dressings remain intact, it is advisable to note the appearance of visible skin and any visible exudate or staining on the outside of the intact dressings. If dressings are being removed or need to be reapplied daily, a full skin evaluation is useful.